The peak one neighborhood: an attainable housing development - Brensing, Brandon Alan (Kansas State University, 2011)
This report examines the Town of Frisco, Colorado development process utilized to implement an attainable housing development within a resort style community. This report begins with the review of historic trends in affordable housing initiatives in American culture that has led to the importance of creating a diverse housing stock. The report was conducted by review of articles, government records, private and public reports, and research on the housing demand and analysis in the regional area. This report was conducted to provide resort style communities, similar to the Town of Frisco, a clear process of implementing an attainable housing development through the use of private/public partnerships. Frisco’s private/public partnership with the development team of Ten Mile Partners serves as a plausible process a community can undertake to increase a community’s housing stock diversity and affordability for long term residents.
Keywords: Affordable housing; Attainable housing; Community Land Trust; Workforce Housing; Urban Planning (0999)